2019
DOI: 10.18632/aging.102432
|View full text |Cite
|
Sign up to set email alerts
|

Aging and stress induced β cell senescence and its implication in diabetes development

Abstract: Cellular senescence is a well-established defensive mechanism for tumor suppression, and is also proposed to play a crucial role in embryonic development, wound repair, aging and age-related diseases. Senescent cell is characterized by the marked morphological changes and active metabolism along with a distinctive senescence associated secretion phenotype (SASP). Cellular senescence is triggered by multiple endogenous and exogenous stressors, which collectively induce three types of senescence. It is believed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 92 publications
(111 reference statements)
0
25
0
Order By: Relevance
“…β-Cells are more sensitive than α-cells to environmental stimuli, as illustrated by studies conducted on islets challenged by metabolic stress mimicking pathophysiological conditions in type 2 diabetes (T2DM) 107 , 108 . In addition to the cytoprotective function, activation of the ER stress sensors is known to lead to a cascade of events promoting direct apoptosis via activation of the IRF–STAT1 pathway 98 , 109 , necroptosis via activation of TNFR1–RIP1 and necrosis by increased production of reactive oxygen species as well as induction of a form of β-cell senescence 108 , 110 , 111 (Fig. 2 ).…”
Section: T1dm As a Disease Of β-Cellsmentioning
confidence: 99%
“…β-Cells are more sensitive than α-cells to environmental stimuli, as illustrated by studies conducted on islets challenged by metabolic stress mimicking pathophysiological conditions in type 2 diabetes (T2DM) 107 , 108 . In addition to the cytoprotective function, activation of the ER stress sensors is known to lead to a cascade of events promoting direct apoptosis via activation of the IRF–STAT1 pathway 98 , 109 , necroptosis via activation of TNFR1–RIP1 and necrosis by increased production of reactive oxygen species as well as induction of a form of β-cell senescence 108 , 110 , 111 (Fig. 2 ).…”
Section: T1dm As a Disease Of β-Cellsmentioning
confidence: 99%
“…Senescent cells are highly metabolically active, but are arrested in the G0 phase of the cell cycle. Mostly, senescent cells acquire characteristic morphological changes like an increase in size, a tremendous re-arrangement of chromatin leading to senescence-associated heterochromatic foci (SAHF), and a distinct gene expression profile [42]. Furthermore, senescent cells can mediate paracrine effects to neighboring cells through secretion of cytokines, chemokines, growth factors, and proteases known as the senescence-associated secretory phenotype (SASP) [43][44][45][46].…”
Section: Cellular Senescence In Pcamentioning
confidence: 99%
“…The SASP components are of diverse nature, including cytokines and chemokines but also a large range of soluble and insoluble factors, and can contribute to immune activation, by promoting infiltration of immune cells. Although further studies are definitely required, it has been recently reported that islets from T1D mice as well as betacells from T1D donors display increased markers of senescence during disease progression (95), suggesting that beta-cell senescence may be an adaptive response to prolonged cellular stress that can contribute to autoimmunity through SASPs (96). Interestingly, studies aiming at eliminating senescent beta-cells by using specific senolytic drugs show remarkable results in limiting T1D progression in mice models (95,97).…”
Section: From Mitochondria Dysfunction To Beta-cell Immunogenicity?mentioning
confidence: 99%